Pengaruh Budaya Organisasi Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PT Taman Jajan Pondok Aren Tangerang Selatan - Rahman Safiih, Abdul; Bagas Prakoso (CV. KAMPUS AKADEMIK PUBLISING, 2025)
he purpose of this study was to determine the influence of organizational culture and work environment on employee performance at PT Taman Jajan Pondok Aren. both partially and simultaneously. The method used in this study is a quantitative method. The sampling technique used is saturated sampling, which uses a sample of 60 respondents. The data analysis technique used is statistical analysis with validity test, reliability test, classical assumption test, simple linear test, multiple linear regression test, coefficient of determination, hypothesis t test and hypothesis f test. The results of the study of organizational culture and work environment on employee performance at PT Taman Jajan Pondok Aren